Accuracy of Apple Watch and Actigraphs during overground and treadmill walking - Dreisbach, Scott; Rhudy, Matthew; Moran, Matthew; Henriquez, Brandon; Veerabhadrappa, Praveen (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Activity trackers monitor activity and health and can track activity progress within the chronic disease population. The purpose of this study was to validate the step counts of the Apple Watch and compare wrist, hip, and ankle-worn Actigraphs during overground and treadmill walking at different walking intensities using video monitoring of participants, with manual step counting as a reference.Methods. The Apple Watch and wrist, hip, and ankle-worn Actigraphs were used for this study. Participants walked on a set track on a flat, overground surface to mimic free-living conditions, with verbal instructions to walk at three stages (slow, moderate, and fast). Subsequently, participants completed a three-stage treadmill protocol using the calculated average velocity/stage from the overground walking. Both conditions were recorded using a Canon VIXIA HF500 camcorder to observe the steps.Results. The Apple Watch had the lowest errors (absolute = –2.32, –8.95, and –20.00 steps; relative = –1%, –2% and –5%) during overground walking for all stages and on the treadmill protocol for the moderate and fast stages (absolute = –3.35 and –2.25 steps; relative = –1% and –1%).Conclusions. The Apple Watch is an extremely accurate and credible consumer device that can be used by the general population for activity monitoring during overground and treadmill walking. The study demonstrated the equivalence of step counts during overground and treadmill walking.
Keywords: Apple Watch; Actigraph; step counts; validation; treadmill; overground